Optineurin in patients with Amyotrophic Lateral Sclerosis associated to atypical Parkinsonism in Tunisian population - Kacem, I.; Sghaier, I.; Peverelli, S.; Abida, Y.; Ben Brahim, H.; Ratti, A.; Nasri, A.; Ticozzi, N.; Silani, V.; Gouider, R. (Amyotrophic lateral sclerosis and frontotemporal degeneration, 2024)
Amyotrophic Lateral Sclerosis (ALS) is a heterogeneous disorder and the phenotypic variability goes far beyond the used clinical stratification parameter. Evidence has emerged that ALS may coexist with distinct neurodegenerative diseases in single cases. We aim to study the clinical features of two familial cases of ALS carriers of two distinct variants harbored in the Optineurin ( ) gene. We included definite familial ALS followed up in the Department of Neurology of Razi University Hospital, Tunisia, and selected according to Byrne criteria. Preliminary screening for the four main ALS genes ( , , , ) was conducted. Given the negative results, we proceeded to NGS target-re-sequencing with a custom panel including genes associated with ALS-FTD, Alzheimer's, and Parkinson's diseases. Both families are carriers of two different variants and they present very different ALS clinical features. The first family comprises two siblings diagnosed with ALS and Corticobasal syndrome (ALS-CBS) at an early age of onset and carriers of p.E135X in the homozygous state. The proband for the second family was diagnosed with ALS at an early age of onset presenting as progressive muscular atrophy with rapid progression. Genetic analysis revealed the presence of the homozygous variant p.R520H. Our findings highlight the peculiarity of genetic Tunisian drift. Indeed, genes with a recessive mode of inheritance may explain part of ALS diversity in clinical features. Therefore, the screening of the gene is highly recommended among inbreeding populations such as the Tunisian one.